Aloe vera gel homogenate shows anti-inflammatory activity through lysosomal membrane stabilization and downregulation of TNF-α and Cox-2 gene expressions in inflammatory arthritic animals - Subhashis Paul; Debabrata Modak; Sutanuka Chattaraj; Deblina Nandi; Aditi Sarkar; Joyjit Roy; Tapas Kumar Chaudhuri; Soumen Bhattacharjee (SpringerOpen, 2021)
Abstract Background Aloe vera leaf gel has proven efficacious roles in the amelioration of several human diseases and illness-conditions. Specific purified gel-derived bio-constituents as well as the naturally harvested unprocessed A. vera gel have shown promise in modifying systemic inflammation. However, the synergistic role of natural herbal remedies, a mainstay of traditional Indian Ayurveda, has not been evaluated rigorously in this plant. In this study, the prevention of membrane lysis and protein denaturation in the presence of A. vera gel homogenate up to the concentration of 1000 μg/ml of gel has been assessed in vitro. Also, regulation of expression of inflammation-mediator genes (TNF-α and Cox-2) has been investigated in vivo in Freund's complete adjuvant (FCA)-induced inflammatory arthritic Wistar albino rats in a 28-day long study following the daily oral supplementation of Aloe vera gel homogenate doses up to 0.40 and 0.80 g/kg body weight (low-dose and high-dose groups respectively). Results Our results indicated that A. vera gel homogenate inhibits hypotonicity-induced (74.89 ± 1.26%) and heat-induced (20.86 ± 0.77%) RBC membrane lyses respectively at a concentration of 1000 μg/ml, compared to indomethacin standard (80.52 ± 0.65% and 43.98 ± 1.52% respectively at 200 μg/ml concentration). The similar concentration of gel also showed 39.35 ± 4.25% inhibition of protein denaturation compared to standard diclofenac sodium (46.74 ± 1.84% at 100 μg/ml concentration) in vitro. When assessed in vivo, TNF-α expression was found to be decreased by 35.88% and 38.52%, and Cox-2 expression was found to be decreased by 31.65% and 34.96%, in low-dose and high-dose groups respectively, when compared to the arthritic controls. Conclusions Our findings justify the role of unprocessed A. vera gel homogenate in preventing tissue damage and in the downregulation of TNF-α and Cox-2 gene expressions for the immune-modulation of inflammatory arthritis condition.